2022
DOI: 10.3389/fncel.2022.816439
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Microglia-Like Cells: Similar but Different

Abstract: Microglia are the tissue-resident macrophages of the central nervous parenchyma. In mammals, microglia are thought to originate from yolk sac precursors and posteriorly maintained through the entire life of the organism. However, the contribution of microglial cells from other sources should also be considered. In addition to “true” or “bona-fide” microglia, which are of embryonic origin, the so-called “microglia-like cells” are hematopoietic cells of bone marrow origin that can engraft the mature brain mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 193 publications
(331 reference statements)
0
25
0
2
Order By: Relevance
“…They interact with neurons via various signaling molecules including transforming growth factor-β (TGF-β), brain-derived neurotrophic factor (BDNF), and complement proteins including CR3 and C1q ( Cornell et al, 2022 ). Epigenome and genome-wide transcriptome studies have shown that microglia are different from other glial cells and tissue macrophages ( Cuadros et al, 2022 ). A number of microglia specific signature genes have been identified to be involved in diverse functions of microglia.…”
Section: Introductionmentioning
confidence: 99%
“…They interact with neurons via various signaling molecules including transforming growth factor-β (TGF-β), brain-derived neurotrophic factor (BDNF), and complement proteins including CR3 and C1q ( Cornell et al, 2022 ). Epigenome and genome-wide transcriptome studies have shown that microglia are different from other glial cells and tissue macrophages ( Cuadros et al, 2022 ). A number of microglia specific signature genes have been identified to be involved in diverse functions of microglia.…”
Section: Introductionmentioning
confidence: 99%
“… 23 At the same time, M2 microglia also release brain-derived neurotrophic factor (BDNF) to promote synapse formation. 23 Therefore, we hypothesized that acupuncture might ameliorate the PSD inflammatory environment, modulate the M1/M2 polarization direction of microglia, upregulate the NRBP1-CREB-BDNF pathway in microglia, and promote synaptic motility by producing more BDNF, thereby improving PSD symptoms, 24 which has also been verified experimentally and subsequently clinically. Combined with relevant literature, the polarization direction of microglia M1/M2 is closely related to the treatment of ischemic PSD, 22 , 25 Sirt1 can inhibit the expression of IL-1, IL-6, TNF-α pro-inflammatory factors, and Sirt1/NF- The κB pathway also plays an important role in regulating microglial M1/M2 polarization.…”
Section: Discussionmentioning
confidence: 96%
“…They supplement the growing concept of glymphatic pathways and warrant further studies to clarify diverging quantitative differences in cases with similar causes of death together with the reason of selective laminar vulnerability at the border of isocortical layers I/II and deep layers V/VI including U-fibers. Forensic autopsy tissue proved invaluable in addressing fundamental neurobiologic and pathologic questions and interpretation of results of animal studies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%